Surgical Morbidity and its Associated Factors in Ovarian Carcinoma - Bhagat, Birendra (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: To estimate 30-day surgical morbidity in patients with ovarian carcinoma and identify its associated factors. Methods: This was an observational study conducted at two cancer hospitals, from October 2020 to March 2021. All women with ovarian carcinoma that underwent surgery were enrolled in the study. Incidence of surgical complications was recorded. Patients were followed up to the 30 th day post- operatively. Logistic regression analyses were used to evaluate the factors affecting surgical complications and their association was determined. Results: A total of 31 patients were analyzed in this study. The incidence rate of surgical complications was 29%. Total 11 complications occurred in nine patients (one intra-operatively and 10 post-operatively). Post-operative complications were wound infection (n=4; 12.9%), urinary tract infection (n=2; 6.4%); one each had post-op ileus, hemorrhage and deep vein thrombosis; and one mortality. Advancing age, increased Body Mass Index, primary surgery, higher surgical complexity score, increased operative time, increased blood loss, higher American Society of Anesthesiologists (ASA) score, presence of chronic disease were associated with surgical morbidity; and their hospital stay was longer (p=0.04). Conclusion: The common complications were wound infection and urinary tract infection.